Homeostasis of lymphocytes and monocytes in frequent blood donors - Ratts, Robert B.; Weng, Nan-Ping (Frontiers in Immunology, 2012)
Age-associated decline of immune function is believed to be largely due to alterations of immune cell regeneration. However, longitudinal changes of human immune cells with age have not yet been adequately addressed. To test the hypothesis that regeneration of lymphocytes and monocytes is robust through most of adult life until advanced age, we examined six leukapheresis donors (3 young and 3 middle-aged/old) who donated approximately 10% of their peripheral blood mononuclear cells (PBMC) every other month over 3-5 years. We found the number of both lymphocytes and monocytes were quite stable in the blood of all six donors. As expected, young donors had more TRECs, more CD31+ cells (CD4 only) and longer telomeres in T cells than did the middle-aged donors. Interestingly, more variation in TREC number, Vβ usages, and telomere lengths were observed in young donors during the 3-5 years course of donation whereas the middle-aged/old donors showed a rather striking stability in these measurements. This may reflect a more prominent role of thymic output in T cell regeneration in young than in middle-aged/old donors. Together, these findings provide an in vivo glimpse into the homeostasis of lymphocytes and monocytes in the blood at different ages, and support the notion that regeneration of lymphocytes and monocytes is robust throughout adult life up to the early 70s.